Structural Analysis of Multi-Storey Steel Frames Exposed to Travelling Fire & Traditional Design Fires: Comparative Analysis of Traditional and Travelling Fire Effects on Multi-Storey Steel Frames (Journal of Advances and Scholarly Researches in Allied Education, 2018)
For understanding of building behaviour in fire, most of the time standard and parametric temperature time fire curves are adopted. However, the disadvantages of design fires on the standard parametric curves are based on small scale tests and also idealize the thermal environment as uniform. Thus, they have important disadvantage on their applicability to large enclosures. But in large open-plan compartments, travelling fires have been observed. To analyse such fires, a design tool called Travelling Fires Methodology (TFM) has been developed used for design. In this paper, the review of study on analysis of multi-storey steel frame in traditional fires travelling fires studied. The comparison between traditional method through parametric curves travelling fires studied.